2019
DOI: 10.25248/reas.e299.2019
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico da sífilis gestacional e congênita na Maternidade Ana Braga – Manaus, Amazonas

Abstract: Objetivo: Avaliar o perfil epidemiológico da sífilis gestacional e congênita na maternidade Ana Braga – Manaus, Amazonas. Métodos: Este estudo foi desenvolvido na Maternidade Estadual, a amostra foi constituída por gestantes VDRL reagente em qualquer momento da gestação e/ou na ocasião do parto, usuárias dessa maternidade e por recém-nascidos com VDRL reagente. Os dados foram obtidos a partir dos prontuários disponibilizados pela maternidade no período de janeiro de 2015 a dezembro de 2017. O projeto foi subme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Confronting the good acceptance of RT in prenatal care and proving that PHC had difficulties in implementing the RTs for syphilis and HIV in the prenatal routine (12) , a study with 376 pregnant women in the period from 2015 to 2017 in Amazonas pointed out that, despite the great adherence to prenatal care (83.5%), 255 (67.8%) only received the diagnosis of syphilis upon admission for delivery (16) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confronting the good acceptance of RT in prenatal care and proving that PHC had difficulties in implementing the RTs for syphilis and HIV in the prenatal routine (12) , a study with 376 pregnant women in the period from 2015 to 2017 in Amazonas pointed out that, despite the great adherence to prenatal care (83.5%), 255 (67.8%) only received the diagnosis of syphilis upon admission for delivery (16) .…”
Section: Discussionmentioning
confidence: 99%
“…Research carried out with 376 cases of congenital syphilis concluded that "although there is a diagnosis and effective treatment for gestational and congenital syphilis, they persist as a serious public health problem since prenatal care is still not of high enough quality and it is not enough to guarantee syphilis control" (16) . Another factor that possibly contributes to the professionals' resistance is a wide history of decisions about the administration of penicillin in PHC in Brazil, as shown in Chart 1.…”
Section: Discussionmentioning
confidence: 99%